Role of Lacosamide in Diabetic Neuropathy: An Experience at Tertiary Care Hospital in Rural Sindh - Mujeeb-ul-Rehman, Zuhaib Ahmed, Ghulam Mujtaba, Aijaz Ali, Shahnaz Shah, Jay Singh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Lacosamide is a relatively newer drug for treatment of chronic diabetic painful neuropathy (CDPN). Objective: To analyse the effectiveness and safety of lacosamide in patients with diabetic neuropathy. Study Design: Randomized controlled clinical trial. Duration and Place of Study: This study was conducted at department of neurology, Khairpur Medical College, Khairpur Mir’s, during from the period Oct 2021 to March 2022. Methodology: Ninety-two patients of either gender, age 20-60 years, known case of diabetes mellitus for minimally 5 years having pain intensity in the range of 4-9 on 11-point (0–10) numerical rating scale & HbA1c value 6.1%-10% were included and assigned randomly (Lacosamide = 46 & Placebo = 46) after taking a valid informed/ written consent. Lacosamide 400 mg/ day was given upto 20 weeks which initially increased from baseline at rate of 100 mg per week. The primary outcome variable was changes from baseline in average pain scores. Results: The mean age of lacosamide group was 40.26±11.33 while in placebo group was 41.30±10.46 years. The mean Pretrial Pain Score measured on NRS of lacosamide group was 6.59±1.95 which decreased to 3.39±1.94 and in placebo group was 6.71±1.89 which decreased to 6.35±1.52 by the end of maintenance phase (20 weeks; p<0.0001). Adverse events (59%) of the patients experience adverse events at least for 1 time. Common side-effects included headache (11% vs. 31%), dizziness (09% vs. 11%), nausea (15% vs. 8%), and diarrhea (8% vs. 19%) with lacosamide and placebo group respectively each (p<0.0001). Conclusion: Lacosamide is a safe and effective drug and achieved in pain relief and may be prescribed as routine treatment of chronic diabetic painful neuropathy. Keywords: Diabetes mellitus, Pain, Chronic diabetic painful neuropathy, Lacosamide, Numerical rating scale